A Tale of Two Hearts: Cardiac Manifestations of Coronavirus-2019. A Case Series and Literature Review - Aloor, Rohit; Aryal, Shravana; Roy, Debajit; Allen, Beth; Saade, Louis; Haas, Christopher James (Archives of Clinical and Medical Case Reports, 2021)
Coronavirus disease 2019 (COVID-19) originally emerged as respiratory disease from a novel coronavirus, SARS-CoV-2. While initial cases revealed a spectrum of respiratory-associated clinical presentations ranging from mild shortness of breath with associated cough to severe respiratory distress, extrapulmonary symptoms, with or without concomitant respiratory disease, have been increasingly reported. Cardiovascular complications are noted in a subset of patients with presentations ranging from non-ST elevation myocardial infarction to fulminant myopericarditis. While cardiac myocytes express the SARS-CoV-2 receptor, Angiotensin converting enzyme 2 (ACE2), the mechanism of cardiac effects remains unknown, further underscoring the complex nature of COVID-19. Here we report two cases of COVID-19 in which cardiac manifestations – pericarditis with associated pericardial effusion and tamponade physiology and fulminant myocarditis – were the predominant manifestation of COVID-19. We hypothesize that many of COVID-19 pulmonary and extra-pulmonary manifestations manifest not only from direct SARS-CoV-2 toxicity in select tissues, but also its interaction with a complex interplay of host factors including genetic and epigenetic modifications of crucial genes – Angiotensin Converting Enzyme 2, Angiotensin Converting Enzyme 1, and Transmembrane protease serine-2 – and their respective affiliation with multiple signaling cascades with resultant dysregulated proinflammatory effects.